PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN PREZI DI KELAS IV SDN 16 PADANG BESI - Puspita, Risma; Fikhen Tri Wulandari, Fikhen Tri Wulandari; Etri wahyuni, Etri Wahyuni; Atri Waldi, Atri Waldi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is a Classroom Action Research (CAR) using qualitative and quantitative approaches implemented in two cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects in this study were teachers and students of grade IV SDN 16 Padang Besi Dalam totaling 27 people in the January-June semester of the 2025/2026 academic year. The research data were in the form of observations of teaching modules, observations of teacher and student activities, and student learning outcomes using the Problem Based Learning model. Data collection techniques were in the form of tests and non-tests. The results of the study showed an increase in learning outcomes for Pancasila Education from cycle I to cycle II. in cycle I began with the results of the analysis of the planning of the teaching module. a) the teaching module showed an average percentage assessment in cycle I of 89.58% (B) increasing to 95.48% (SB) in cycle II. b) the implementation of the teacher aspect in cycle I obtained an average of 82.14% (B) increasing to 96.42% (SB) in cycle II. While the implementation of the student aspect in cycle I obtained an average percentage of 77.77% (C) increasing to 92.96% (SB) in cycle II. c) assessment of learning outcomes in the attitude aspect of cycle I obtained an average of 76.53 (C) increasing to 88.26 (B) in cycle II. Then in the knowledge aspect of students in cycle I obtained an average of 77.77 (C) increasing to 92.96 (SB) in cycle II. Assessment of learning outcomes of skills in cycle I obtained an average value of 73.40 (C) increasing to 90.74 (SB) in cycle II. Thus, it can be concluded that the Problem Based Learning Model can improve student learning outcomes in the Pancasila Education Subject of grade IV SDN 16 Padang Besi.